2021
DOI: 10.17060/ijodaep.2021.n1.v1.2083
|View full text |Cite
|
Sign up to set email alerts
|

Depressão e pandemia: estudo com universitários brasileiros

Abstract: A depressão é uma doença incapacitante, crônica e recorrente. Tem como sintomas humor deprimido, desprazer em atividades que antes geravam prazer, perda ou ganho significativo de peso por alteração no apetite, insônia ou hipersonia, falta de energia, sentimento de culpa, dificuldade de se concentrar, baixa autoestima, irritabilidade, ansiedade, e, em casos graves, pode levar ao suicídio. Pode ser classificadas como leve, moderada ou grave de acordo com a intensidade dos síntomas. Essa doença pode piorar em div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Accordingly, the percentage of depressive symptoms in this study was higher than the 40% found in the general Brazilian population [70], whereas worldwide, a range from 14.6% to 48.3% has been reported [94]. In addition, it was higher than the results of previous studies with Brazilian university students (eg, 29% [95]), although lower than those of Brazilian undergraduate students (60.5% [22]). Internationally, university students have reported percentages of depressive symptoms ranging from 34% to 37% [21,30] (the studies did not distinguish between undergraduate and graduate students).…”
Section: Clinical Practices For Students' Mental Healthcontrasting
confidence: 82%
“…Accordingly, the percentage of depressive symptoms in this study was higher than the 40% found in the general Brazilian population [70], whereas worldwide, a range from 14.6% to 48.3% has been reported [94]. In addition, it was higher than the results of previous studies with Brazilian university students (eg, 29% [95]), although lower than those of Brazilian undergraduate students (60.5% [22]). Internationally, university students have reported percentages of depressive symptoms ranging from 34% to 37% [21,30] (the studies did not distinguish between undergraduate and graduate students).…”
Section: Clinical Practices For Students' Mental Healthcontrasting
confidence: 82%